Drug Levels in the Maternal Serum, Cord Blood and Breast Milk of a Ustekinumab-Treated Patient with Crohn's Disease - Klenske, Entcho; Osaba, Lourdes; Nagore, Daniel; Rath, Timo; Neurath, Markus; Atreya, Raja (Journal of Crohns & Colitis, 2019)
Ustekinumab [UST] therapy during pregnancy has not yet been extensively evaluated in patients with Crohn's disease. Here, we present the case of a 24-year-old woman with therapy-refractory Crohn's disease, who was treated with UST until Week 30 of pregnancy and successfully delivered a healthy baby boy, who had normal development in the follow-up period of one year. The cord blood UST level was markedly higher than the measured maternal serum drug level. The trough level in the breast milk after re-initiating postpartum UST therapy was initially in the same range as the corresponding serum trough level, and then decreased during maintenance therapy. This is one of the first reports describing the drug levels in the breast milk after re-initiating UST treatment in a Crohn's disease patient.
CRIS-Team WoS Importer:2019-03-06